PROFESSIONAL DEVELOPMENT OF PERSONNEL IN THE CONDITIONS OF INTERNATIONAL ECONOMIC ACTIVITY OF ENTERPRISES - Kara , N.I.; Phsyk-Kovalska , O.O. (The actual problems of regional economy development, 2018)
The article is aimed at the study of theoretical and practical aspects of professional development of the personnel of the enterprise in the conditions of international economic activity. The article deals with the stages and main tasks of the personnel development process of the organization, as well as the process of planning the career development of the employee. Also, the methods of personnel development are considered and the main priorities, factors and peculiarities of management of personnel professional development of international companies are highlighted. It is proposed to introduce a program of corporate training of employees, in particular the use of intranet portal, which will increase the efficiency of the enterprise through the systematic development of knowledge and competences of employees.